Depredatory effects of the parasitoid Cephalonomia stephanoderis on the immatures stages of Hypothenemus hampei in field conditions - ARISTIZÁBAL-A., LUIS F.; BUSTILLO-P., ALEX E.; BAKER, PETER S.; OROZCO-H., JAIME; CHAVES-C., BERNARDO (Revista Colombiana de Entomología, 1998)
The coffee berry borer (CBB, Hypothenemus hampei) is the world’s most important coffee pest. In Colombia an Integrated Pest Management Programme is being developed for this pest, whose principal components are cultural control, biocontrol, and when absolutely necessary, chemical control. One of the most promising natural enemies of the CBB is the parasitoid C. stephanoderis. Apart from its parasitic action on the immature stages, it has also been observed to act like a predator. As there are no experimental studies on this aspect, the aim of this study was to quantify the predator action of this wasp under field conditions. The experiments were carried out in the Rafael Escobar experimental substation at Supía, Caldas, 1320 m above sea level, 21,9 °C mean annual temperature, 2020 mm rainfall, and 75% RH, in a plot of 3-year-old Coffea arabica var. Colombia. Previously uninfested berries were infested artificially with CBB in entomological sleeve cages around the branches. Wasps were released for treatments of 5,10 and 15 days after infestation either (a) inside the sleeves, (b) free field release, or (c) control. Four destructive samples were taken at 3, 10, 20, and 30 days after wasp release. For the controls, there were means of 10, 13, and 15 CBB stages per berry at 5, 10, and 15 days after infestation. For the sleeve cages there were 3, 5, and 6 stages and for the open field treatment, 4, 7, and 8 stages per berry. These latter two were significantly lower than the controls. The wasps reduced the CBB population by 65% in the cages and 49% in open field conditions, demonstrating their effectiveness as predators. The extra mortality caused by predation may thus significantly enhance their effectiveness as control agents of CBB.